The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00125-016-4200-4
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth and the risk of type 2 diabetes in adulthood: a prospective cohort study of 0.5 million Chinese adults

Abstract: Aims/hypothesis Season of birth as a surrogate for potential environmental exposure during fetal development and early postnatal life has shown an inconsistent association with adult type 2 diabetes in white populations living in high-latitude regions. The present study aimed to examine the association between birth seasonality and risk of adult type 2 diabetes in Chinese individuals living across wide regions of low latitude and lower to middle latitude. Methods Participants from the China Kadoorie Biobank we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
0
16
2
1
Order By: Relevance
“… 35,36 Furthermore, maternal exposure to cold spells and changes in nutrients and lifestyles intervenes with BP through changing DNA methylation status of the offspring. Small observed changes in methylation status can lead to large phenotypic differences that contribute to altered susceptibility to certain diseases later in life 6‐11,17,23‐27,33,36 . However, further studies are warranted to explore the underlying mechanisms that link season of birth and hypertension in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 35,36 Furthermore, maternal exposure to cold spells and changes in nutrients and lifestyles intervenes with BP through changing DNA methylation status of the offspring. Small observed changes in methylation status can lead to large phenotypic differences that contribute to altered susceptibility to certain diseases later in life 6‐11,17,23‐27,33,36 . However, further studies are warranted to explore the underlying mechanisms that link season of birth and hypertension in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of hypertension are complex and multi‐factorial, where environmental factors play important roles such as exposure to low temperatures (cold spells) 2,3 . In addition, recent research has demonstrated that exposure to unfavorable environmental stimuli early in life is another important determinant of the risk of hypertension and associated conditions during adulthood 4‐6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirically, studies of time-of-year of birth associations with DM have been inconsistent for many years (Didikoglu et al 2020;Jensen et al 2015;Rothwell et al 1999;Si et al 2017;Vaiserman et al 2009;Zhao et al 2000). Recently, a season of birth association with DM (also with potential effect modification by latitude) was observed in the large China Kadoorie Biobank analysis of 0.5 million people with summer birth seemingly being protective (Si et al 2017). In contrast, no association with season of birth is described in the 0.5 million participant UK Biobank (Didikoglu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal patterns of type 2 diabetes mellitus (T2DM) have been noted extensively. T2DM seasonal patterns were related to glucose control [1,2,3,4], temperature [5,6,7,8], Vitamin D [9,10,11,12], birth season [13,14,15,16], insulin sensitivity [17,18,19], and hypoglycemia [20,21]. Seasonal variation of type 2 diabetes exists within components of the metabolic syndrome, such as glycaemia, which is significantly higher in winter attributed to multiple causes including seasonal checkups, low temperature, and affective disorder [6].…”
Section: Introductionmentioning
confidence: 99%